Experimental study into the propagation and attenuation of blasting vibration waves in porous rock-like materials - Lu, Ge; Tao, Yuhang (Frontiers in Materials, 2023)
Rock blasting vibration can cause harm to the surrounding environment. This article aims to investigate the propagation and attenuation of vibration waves in the blasting excavation of porous rock. Similar materials were used to simulate porous rock media and indoor blasting experiments were conducted on 12 porous rock-like models poured to estimate influences of the media material, porosity, moisture conditions, and decoupling coefficient of blast holes on the propagation of blasting stress waves. The results show that: (1) the crack propagation path of vibration waves in foam ceramics similar materials (FC) is not a completely straight line: cracks tend to produce a large deflection during the development process; (2) damage modes of low-porosity similar materials are mainly dominated by crack development, while damage and failure of high-porosity similar materials involve crack expansion and crushed fragments; (3) the peak vibration acceleration presents exponential decay with the distance, which will not vary with changes in the media material, porosity, moisture conditions, and the decoupling coefficient of blast holes; (4) the peak vibration acceleration of cementbased similar materials (SM) demonstrates the exponential decay coefficient of -1.4 ~ -1.0, the exponential decay coefficient of the peak vibration acceleration for FC is -0.8 ~ -0.4. The peak vibration acceleration of high-porosity similar material shows a faster decay rate, which is generally 0.3 less than that of the low-porosity similar material; (5) the type of material exerts the most significant controlling effect on the decay coefficient of peak vibration acceleration, followed by the effects of porosity and degree of water saturation; the decoupling coefficient of blast holes does not exert any significant influence on the decay of peak vibration acceleration.